The Students’ View on the Impact of Teacher Overcorrection on Their Confidence and Motivation in the EFL Classroom - Fitra Ramadani; Rika Nurdini (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study investigates the effects of teacher overcorrection on student confidence and motivation in English as a Foreign Language (EFL) speaking classrooms in Indonesia. Despite its importance, the relationship between error correction, student anxiety, and linguistic development remains understudied in Indonesian contexts. This research explores the perceived impact of teacher overcorrection on student self-confidence and motivation, with a focus on the 12th-grade students of SMAN 1 Alalak. The study adopts a qualitative case study approach, triangulating data from teacher interviews, student reflective journals, and preliminary questionnaires. The findings reveal a paradox between teacher intentions and student experiences, with overcorrection undermining student confidence and fostering a fixed mindset. The study highlights the need for teacher training in emotionally intelligent correction practices, balanced assessment methods, and student-centered feedback approaches to promote a growth mindset and enhance fluency development in Indonesian EFL learners